Immunological Resistance of Pseudosuccinea columella Snails From Cuba to Fasciola hepatica (Trematoda) Infection: What We Know and Where We Go on Comparative Molecular and Mechanistic Immunobiology, Ecology and Evolution - Alba, Annia; Vázquez, Antonio A.; Sánchez, Jorge; Gourbal, Benjamin (Frontiers in Immunology, 2022)
One of the most interesting biological models is that of snail-trematode interactions, many of which ultimately result in the transmission of several important diseases, particularly in the tropics. Herein, we review the scientific advances on a trematode – snail system in which certain populations of Pseudosuccinea columella (a common host species for trematodes) have been demonstrated naturally-resistant to Fasciola hepatica, in association with an effective encapsulation of the parasite by host’s innate immune cells, the hemocytes. Emphasis is made on the molecular and immunological features characterizing each P. columella phenotype in relation to their anti-parasitic competence, their distinctive ecological patterns and the existence of a significant cost of resistance. An integrative overview of the resistance to F. hepatica through comparative immunobiology, genetics and ecology is presented to hypothesize on the possible origins and evolution of this phenomenon and to postulate significant roles for parasite mediated-selection and environmental factors in shaping and maintaining the resistant phenotype in the field. Lastly, clues into future experimental perspectives to deeply characterized the interplay between P. columella – F. hepatica and the immunobiology of the resistance are also included. The advances revised in the present paper are only beginning to unravel mechanisms of anti-parasite innate defense responses and their evolutionary bases, and can facilitate the development of prospective approaches towards practical applications of P. columella resistance.